Memadukan Konsep Kecerdasan Intelektual, Emosional, Spiritual dan Ruhaniah Dalam Proses Pendidikan - Muzhoffar Akhwan (Islamic University of Indonesia, 2002)
The substation of Education is child’s growth proceed in order to independent in the future to solution of their life problems. In order to of the child's education can be succeed. That's way educator (parents and the teacher) must understand the child based potential is adult tendentious imitate. Education through example and to accustom oneself of behavior and word are relevant to children period. The educational method with model (al-tarbiyah bi al-qudwah) and good wise and right can be impressed at child whom finally will get used to behavior daily. For strengthen imitate push which good and right can be used reward (tsawaab, in Islamic educational system should be highly motivated by this reward. Punishment (iqaab) or hit United State of America strenphens in order to not to be adopted. In the Islamic System corporal punishment is recognized and regarded United State of America as an effective means of correction. Remind of parents and that of teacher are important, that's way between parents education and the teacher must help each others not contradictive about the content of any curriculum which are taught or behavior which showed to the children.Key Word: Child's Education, islamic Education System